Does lower water availability limit stem CO2 efflux of oak and hornbeam coppices? - Darenova, Eva; Knott, Robert; Vichta, Tomáš (AoB PLANTS, 2024)
Recent changes in water availability can be crucial for the development, growth and carbon budget of forests. Therefore, our aim was to determine the effect of reduced throughfall and severe summer drought on stem CO2 efflux as a function of temperature and stem increment. Stem CO2 efflux was measured using the chamber method on oak and hornbeam under four treatments: coppice, thinned coppice, and both coppice and thinned coppice with 30 %-reduced throughfall. The first year of the experiment had favourable soil water availability and the second year was characterized by a dry summer. While reduced throughfall had no effect on stem CO2 efflux, the summer drought decreased efflux by 43-81 % during July and August. The stem CO2 efflux was reduced less severely (by 13-40 %) in September when the drought persisted but the stem increment was already negligible. The stem increment was also strongly affected by the drought, which was reflected in its paired relationship with stem CO2 efflux over the two experimental years. The study showed that summer dry periods significantly and rapidly reduce stem CO2 efflux, whereas a constant 30 % rainfall reduction needs probably a longer time to affect stem properties, and indirectly stem CO2 efflux.
Keywords: Carpinus betulus; stem respiration; soil water content; Quercus petraea; stem growth; summer drought